Colonic Strictures in Inflammatory Bowel Disease: Epidemiology, Complications, and Management. (12th April 2021) - Fumery, Mathurin; Yzet, Clara; Chatelain, Denis; Yzet, Thierry; Brazier, Franck; LeMouel, Jean-Philippe; Laharie, David; Sabbagh, Charles
Abstract: The management of colorectal stricture complicating inflammatory bowel disease [IBD] remains a challenging condition. Stricture raises concern about neoplastic complications, which cannot be fully ruled out by negative endoscopic biopsies. Also, impassable strictures restrict the endoscopic monitoring of upstream disease activity and dysplasia. Surgery remains the 'gold standard' treatment for colonic strictures but is associated with high morbidity. Over the past few decades, our therapeutic arsenal for IBD has been reinforced by biologics and therapeutic endoscopy. Few studies have focused on colonic strictures, and so current therapeutic strategies are based on a low level of evidence and applied by analogy with the treatment of ileal strictures. With a view to facilitating the decision making process in clinical practice, we reviewed the literature on the epidemiology, natural history, and management of colonic strictures in IBD.